User Centered Governance and Digital Integration for Inclusive Public Transport: Insights from Palu City - Wasil, Mohammad; Wijayanti, Dian; Pahrudin, Cecep (Logistica : Journal of Logistic and Transportation, 2025)
Urban transportation in mid-sized cities often faces declining reliability and inclusivity. This study examines Palu City, Indonesia, where conventional public transport has sharply decreased while app-based services dominate user preference. Using a qualitative descriptive approach with 42 informants including commuters, drivers, officials, and civil society representatives data were collected through interviews, observations, and document review. Findings show that angkot and BRT services suffer from unreliable schedules, poor vehicle conditions, and limited accessibility, especially for elderly and disabled users, while app-based services achieve satisfaction above 90% due to convenience and transparency. Governance constraints include fragmented policies, limited funding, and lack of digital tools. The study recommends four key reforms: (1) user-centered service standards on reliability and safety; (2) inclusive infrastructure with universal design; (3) digital integration through real-time tracking and fare systems; and (4) collaborative governance involving communities and operators. This research is the first systematic evaluation of user satisfaction across multiple transport modes in Palu, contributing a multidimensional framework that links user perceptions with strategic policy recommendations for sustainable mobility in secondary cities.